(untitled) (Unity Journal, 2025)
The Nepal-Tibet-China War (1791-92) was a noteworthy event in the geopolitical history of the Himalayan area, marked by the decisive generalship of Chautariya Bahadur Shah of Nepal and Fuk’anggan of the Qing dynasty. During this conflict, Nepal, led by Chautariya Bahadur Shah, aimed to preserve Nepali influence over Tibet. Bahadur Shah was one of the important military and political leaders of the newly united modern Nepal who carried out a strategy of unification in the Himalayas following the path of his father, Great King Prithvi Narayan Shah. Both strategic interests and the goal to strengthen Nepal’s regional power led Nepali troops to penetrate the Tibetan plateau. Though the initial conflict was limited to Nepal and Tibet, Tibetan leadership requested Chinese assistance in the war. Chinese authorities considered Tibet as a region within their sphere of control. Fuk’anggan, the governor of Xining and a senior military general of the Qing dynasty of the Chinese empire, was assigned the responsibility of thwarting the Nepali progress. Fuk’anggan was considered the most influential personality in the Chinese court. Fuk’anggan’s military tactics were marked by greater force and a resolute offensive, helping to push Nepali troops to retrograde in defensive positions. The dispute involving Bahadur Shah and Fuk’anggan was characterized by a succession of intense military confrontations and intricate diplomatic strategies. The war resulted in high casualties and resource depletion for both sides. With both warfare and negotiations, a ‘no loser’ situation for both China and Nepal was set. The final solution was achieved by treaties that defined fresh borders and made adjustments. Methodologically, this study examines the involvement of Bahadur Shah and Fuk’anggan in the war using a multi-step approach. This includes analyzing old texts and academic papers, studying primary sources such as treaties and official documents, and referring to secondary sources for background information. An examination of military strategies and leadership styles, as well as an investigation into the geopolitical context, is carried out. Data were collected and analyzed to draw a deep understanding of the research questions. The article has sought some distinct similarities and differences between the great leaders in terms of their personal characters and leadership traits.